Dasar Pertimbangan Penetapan Nilai Limit Obyek Lelang Eksekusi Hak Tanggungan - Fahmi, Herzie Riza; Negara, Tunggul Anshari Setia; Kawuryan, Endang Sri (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This study aims to analyze the legal considerations used by the head of the district court in the adjudicate the auction of execution. The other purpose is to analyze the legal implications related to the enactment of the Security Rights Law and the Minister of Finance’s Regulation on Instructions for Auction Implementation. This study uses normative juridical research with a statute approach and a case approach. The results show that there are three basic considerations used by the head of the district court in determining the object's limit value over the auction of security rights execution. The juridical implication that the head of the district court is wrong in applying Article 6 of the Security Rights Law. The determination of the limit value by the head of the district court contrary to the principle of the judge being passive and waiting.